TINJAUAN STANDARISASI LABORATORIUM IPA DI SMP NEGERI SE- KABUPATEN PASAMAN BARAT - Maulidiyah, Rizky - (Pendidikan Biologi, 2014)
The realization of optimal learning science can be done by conducting laboratory experiments. Laboratory as a learning infrastructure in schools, serves as a place for practicum. Practical activities can provide a real experience for students. Therefore, the laboratory plays an important role as a source of learning for students to achive the expected learning science competencies. This research is aimed to determine the standardization of science laboratory in Junior High School of West Pasaman district. This research is a descriptive which is conducted in Juli â September 2014, with a sample of 11 schools in the science laboratory in Junior High School of West Pasaman district. The type of data in this research is primary data collected directly from respondents throught a questionnaire. The research instrument is a questionnaire that given to the laboratory manager/teacher who is teaching sciences. The data is analyzed by using descriptive statistics and qualitative percentage. From the analysis of the result, it shows that the percentage of the average in the science laboratory standardization in Junior Hight School of West Pasaman is 64,05 % which is the sufficient criteria. Therefore, it can be concluded that science laboratory standardization in Junior High School of West Pasaman is sufficient to meet the standars set by the Minister Regulation No. 24 Tahun 2007.